Should the state aid prohibition impact the property tax legislation in EU member states? - Kałążny, Adam (Bulletin of the Karaganda University “Law Series”, 2023)
Purpose of the article is to present the problem of applying the state aid rules (binding in EU) to the nonharmonized taxes such as property taxes, which differ strongly between Member States. The tax exemption from the real estate tax for the railway infrastructure which was introduced in Poland will be a subject to the investigation of Court of Justice of the European Union (CJEU). CJEU should answer to the question if the tax exemption from property tax in one Member State may be treated as a prohibited benefit granted to the entrepreneurs, having in mind that the same kind of property may be taxed significantly lower, or even not taxed at all in the other EU Member States. The verdict of CJEU will be important for the Polish entrepreneurs, but also will be significant for the tax policy in the EU. In case of the CJEU judgment declaring that the property tax exemption introduced by Poland constitutes illegal state aid it will be necessary to consider whether countries that do not tax the certain categories of property (or tax them at a very low level) do not grant illegal state aid to their entrepreneurs.